Pendampingan Wirausaha Berbasis Modul ILO Score Training di Toko Shanti Bhuana - Oliviana Santaria; Brujo Ardulat; William Wendy Ary (LPPM ITB AAS Indonesia Surakarta, 2022)
Community service in the form of mentoring MSMEs is an activity related to the tridrama of higher education which is closely related to today's daily life, especially in the all-digital era. Based on data from the Indonesian Central Statistics Agency (BPS), Indonesian MSMEs have contributed 60.3% of Indonesia's total Gross Domestic Product (GDP). However, only 13% of the total MSMEs make good use of technological advances. One of the MSMEs that have not implemented the digital era as an opportunity is Shanti Bhuana Shop. The assistance provided to the Shanti Bhuana Shop SMEs to help Shanti Bhuana Shops implement ILO Score Training as a means to facilitate Shanti Bhuana Shops in compiling a business model or creative and innovative business. The assistance and management that will be carried out for Shanti Bhuana Stores is to introduce ILO Score Training and Google My Business. The methods applied in the service to the Shanti Bhuana Shop are lectures, tutorials, and practices. During the mentoring program, scheduled activities have been implemented. From the mentoring and management program to the Shanti Bhuana Shop. The result of this service is where Shanti Bhuana Store itself has successfully implemented ILO Score Training and Google My Business with intense assistance. It is estimated that the visits and sales of Shanti Bhuana's shop will increase after successfully implementing the ILO Score Training and Google My Business. Kata kunci: MSME, Shanti Bhuana Shop, Google My Business, ILO Score Training and Community